Monitoring and evaluating eco-localisation: Lessons from UK low carbon community groups. (July 2016) - Hobson, Kersty; Mayne, Ruth; Hamilton, Jo
In the UK 'low carbon' community groups and partnerships (LCCGPs) have flourished in recent years, with sectors such as community energy receiving increased national policy attention. Whilst such attention aligns LCCGPs with agendas such as 'New Localism' and climate change mitigation, other modes of local socio-environmental change are advocated and enacted under a broad rubric of 'eco-localisation'. Across the political and ideological spectrum however, there is growing interest in how LCCGPs understand and evaluate their impacts, with questions arising about what indicators, processes and tools are most pertinent and rigorous. In response, this paper draws on a knowledge exchange project that explored and trialled monitoring and evaluation (M&E) tools amongst a sample of UK LCCGPs in conjunction with groups and networks operating in an eco-localisation vein. Project findings highlight the positive effects that flexible and relevant M&E has on groups and networks. It also draws attention to the need for on-going support and facilitation for those undertaking M&E: vital if the burgeoning 'impact agenda' – whether emerging from central funders or 'eco-localist' networks themselves – does not over-burden or dishearten groups, thus causing the opposite effects of tools and processes meant to facilitate sustained and shared thinking, learning and action.